Pengaruh Kualitas Pelayanan dan Word of Mouth Terhadap Loyalitas Konsumen Melalui Kepuasan Konsumen Pada Pecel Lele Monggo Mampir Tanjungpinang - Nabilah Putri; Iranita Iranita; Lastri Anggi Fani (CV. Rumoh Aceh Publishing, 2026)
This study aims to analyze the effect of service quality and word of mouth on consumer loyalty through consumer satisfaction at Pecel Lele Monggo Mampir Tanjungpinang. The study used a quantitative approach with a purposive sampling technique on 96 consumers. Data were collected through questionnaires and analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with the SmartPLS 4.0 application. The results showed that service quality had a positive but insignificant effect on consumer loyalty, while word of mouth had a positive and significant effect on consumer loyalty. Service quality had a positive and significant effect on consumer satisfaction, while word of mouth had a positive but insignificant effect on consumer satisfaction. Consumer satisfaction had a positive and significant effect on consumer loyalty and mediated the effect of service quality on consumer loyalty, but did not mediate the effect of word of mouth on consumer loyalty. These findings indicate the importance of improving service quality and strengthening word of mouth promotion to increase consumer loyalty.